An examination of transaction interdependency: a perspective in the animal health and nutrition industrial system - Harris, Keith D.; James, H. S. Jr (My University, 2014)
The research examining bioscience networks has been studied from two perspectives. One view comes from economics and the other sociology. We examine the technical (material flows) and people aspects (information sharing) of interdependency in the context of economic exchanges in a bioscience network. The empirical contributions are the techniques used to explain the network structure of a burgeoning animal health and nutrition bioscience network and the portability of network analysis concepts that provides the potential to manage diverse business networks. The results suggest the economic exchanges can be traced back to the underlying interactions that safeguard transactions and influence the flow of resources and information.
Keywords: Transaction costs; Networks; Bioscience; Social